2022
DOI: 10.3390/life12081288
|View full text |Cite
|
Sign up to set email alerts
|

Tff3 Deficiency Protects against Hepatic Fat Accumulation after Prolonged High-Fat Diet

Abstract: Trefoil factor 3 (Tff3) protein is a small secretory protein expressed on various mucosal surfaces and is involved in proper mucosal function and recovery via various mechanisms, including immune response. However, Tff3 is also found in the bloodstream and in various other tissues, including the liver. Its complete attenuation was observed as the most prominent event in the early phase of diabetes in the polygenic Tally Ho mouse model of diabesity. Since then, its role in metabolic processes has emerged. To el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…When looking further into these differences and changes following the HS diet, there seems to be a genetically determined predisposition regarding pro-inflammatory IL-6, as it was higher when lacking Tff3 . The same effect was observed following a high-fat diet in knock-out mice, where IL-6 upregulation was associated with a sort of a protective role in the absence of Tff3 when it came to metabolic disorders [ 39 , 40 , 41 ]. It was also found that (3) CD25 expressing T cell rates (MLN) were significantly higher in TFF3ko mice compared with the baseline rates in WT mice.…”
Section: Discussionmentioning
confidence: 66%
“…When looking further into these differences and changes following the HS diet, there seems to be a genetically determined predisposition regarding pro-inflammatory IL-6, as it was higher when lacking Tff3 . The same effect was observed following a high-fat diet in knock-out mice, where IL-6 upregulation was associated with a sort of a protective role in the absence of Tff3 when it came to metabolic disorders [ 39 , 40 , 41 ]. It was also found that (3) CD25 expressing T cell rates (MLN) were significantly higher in TFF3ko mice compared with the baseline rates in WT mice.…”
Section: Discussionmentioning
confidence: 66%
“…We found that Tff3-deficient males (21 weeks old) had significantly reduced body weight, which could not be noticed at later stages (age 36 weeks and 40 weeks) of HFD feeding [46]. Tff3-deficient females exhibited no such body weight time line variation, but at the end point (40 weeks), they had significantly lower blood glucose levels (Figure 1) [46].…”
Section: Discussionmentioning
confidence: 83%
“…The novel congenic mouse Tff3-/-/C57BL/6NCrl, without additional mutations present in the C57Bl/6J strain and without the impact of unintentional genetic variants due to a mixed genetic background, was fed a HFD to determine the impact of Tff3 deficiency and Tff3 protein function in this disease-related model that appears to include some adaptation mechanisms [45]. We found that Tff3-deficient males (21 weeks old) had significantly reduced body weight, which could not be noticed at later stages (age 36 weeks and 40 weeks) of HFD feeding [46]. Tff3-deficient females exhibited no such body weight time line variation, but at the end point (40 weeks), they had significantly lower blood glucose levels (Figure 1) [46].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations